THE RELATIONSHIP AMONG FAMILY MEMBERS AND MENTAL HEALTH OF THAI ADOLESCENTS - Phornthip Chuayphen; Apisada Srikhruedong (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2019)
This study aimed to investigate the relationship among family members and mental health level of Thai adolescents. This quantitative research obtained secondary data from the Survey on Conditions of Society, Culture and Mental Health (Thai Happiness) conducted by the National Statistical Office in 2014. The samples were 3,840 adolescents aged 15 – 24 years. Data were analyzed by using descriptive and multiple linear regression analysis. The results show that Thai adolescents have an average mental health score at a high level (33.27 points).Types of relationship among family members that positively affect adolescents’ mental health the most are ‘Having happy family time together for outdoor activities’, ‘Discussing or engaging on important issues for the family’ , ‘Loving, understanding and supportive behavior for family members, ‘Being a well-behaved members of the family’, and ‘Taking part with family members for any kind of family activities’ .However, Emotional conflict or use violence in solving family problems. has negative relationship with mental health. Age education family characteristics and level of physical well-being are found to have statistically significance related to mental health of adolescents at p ≤ 0.05. This study recommends family members doing activities together or build good relationships within the family. To reduce the stress of adolescence can lead to mental health problems